Potential impact of large ungulate grazers on African vegetation, carbon storage and fire regimes. Issue 9 (29th April 2015) - Pachzelt, Adrian; Forrest, Matthew; Rammig, Anja; Higgins, Steven I.; Hickler, Thomas
Abstract Aim Large ungulate grazers have been a fundamental component of African savannas since the spread of the savanna ecosystem in the Miocene. The magnitude of the impact of ungulates on vegetation has been debated for a long time, but quantifying such effects at the continental scale has been difficult. This study presents an attempt to estimate for the first time the potential impact of large natural ungulate grazer herds on African ecosystems. Location The African continent (excluding Madagascar). Method The potential impacts of grazing on grass biomass, competition between grasses and trees, the occurrence and effects of wildfire and biome distribution were simulated with a model that couples a physiological grazer population model with a physiological dynamic vegetation one (not including the effects of browsing). This model has previously been shown to reproduce grazer densities across African wildlife reserves. Results Modelled grazer densities corresponded reasonably well with the continental distribution of African grazers represented by the herbivore functional types in the model. The coupled model predicted a hump‐shaped relationship between annual precipitation and grazer biomass densities within a range of estimates from independent studies. In accordance with other studies, net primary productivity and the length of the dry season were the strongest predictors of grazer densities in the model. The inclusion of grazers in the model did not substantially alter an already (without grazers) reasonable fit between simulated vegetation biomass and burned area and estimates of these derived from remote sensing data. Nevertheless, the grazer–vegetation model predicted substantial impacts on grass biomass, tree biomass and burned area, particularly in areas with high grazer densities. The biome distribution at the continental scale, however, was similar with and without grazers. Main conclusion The results suggest that natural large ungulate grazers have been important drivers of ecosystem functioning in some savanna ecosystems, but also that they do not have a large effect on the continental‐scale biome distribution and carbon stocks.